PERBEDAAN BONDING ATTACCHMENT PADA IBU POST SECTIO CAESAREA DENGAN IBU POST PARTUM NORMAL DI RSUD S.K LERIK KOTA KUPANG - Lenawati Sembiring; Sakti Oktaria Batubara; Erna Febriyanti (CHMK MIDWIFERY SCIENTIFIC JOURNAL, 2021)
Bonding attachment is very important and beneficial for mother and baby because it will provide comfort and high confidence for the baby, and will increase the hormone oxytocin and prolactin associated with uterine contractions and breastfeeding for mother. Delay in the bonding attachment process will affect the child's emotional level and self-confidence. To find out the difference between bonding attachment on post sectio caesarean mothers and normal post partum mothers at RSUD S.K. Lerik in Kupang City.This study used an ex-post facto research design which research on independent variables have occurred when the study began with a sample of 60 people, taken using a sampling technique. Most of the Post Sectio Caesarean mothers have Bonding Attachments in the adequate category and most of the Post Normal Partum Mother have Bonding Attachments in good category. Statistical test results used the U-Mann-Whitney test obtained a mean value of 26.00, p value 0.025 (p <0.05). So it can be concluded that there was a difference between bonding attachment on post sectio caesarean mothers with normal post partum mothers at RSUD SK Lerik Kupang City, and statistically significant. Experience, mother emotional health, social support and good mobilization will increase the bonding attachments given to the baby. Keywords: Bonding Attachment, Post Sectio Caesarea, Normal Post Partum